Studi Korelasi antara Kompetensi Multikultural dengan Perilaku Moral Mahasiswa di Prodi PGSD Universitas Sarjanawiyata Tamansiswa - Dwi Wijayanti; Wachid Pratomo; Dyan Desi Madyarini; Mutiara Mega Pratiwi; Arya Dani Setyawan (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2026)
This study examined the relationship between multicultural competence and students' moral behavior among Elementary School Teacher Education (PGSD) students at Universitas Sarjanawiyata Tamansiswa Yogyakarta. A correlational research design was employed involving 38 students. Data were collected using a closed-ended rating scale questionnaire. Instrument validity was assessed using the Pearson Product-Moment correlation, while reliability was tested with Cronbach's Alpha. Data analysis included normality and linearity tests, followed by simple linear regression to examine the proposed relationship. The findings revealed a significant positive relationship between multicultural competence and students' moral behavior. The regression analysis produced an R² value of 0.709, indicating that multicultural competence accounted for 70.9% of the variance in students' moral behavior, while the remaining 29.1% was explained by other factors. These results support the alternative hypothesis, suggesting that higher levels of multicultural competence are associated with more positive moral behavior. Strengthening multicultural competence in higher education may therefore contribute to fostering students' moral development.